2014
DOI: 10.1021/ja500992b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Formation from Proximal Glycol Pairs on TiO2(110)

Abstract: Understanding hydrogen formation on TiO2 surfaces is of great importance, as it could provide fundamental insight into water splitting for hydrogen production using solar energy. In this work, hydrogen formation from glycols having different numbers of methyl end-groups has been studied using temperature-programmed desorption on reduced, hydroxylated, and oxidized rutile TiO2(110) surfaces. The results from OD-labeled glycols demonstrate that gas-phase molecular hydrogen originates exclusively from glycol hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(59 citation statements)
references
References 35 publications
5
54
0
Order By: Relevance
“…35 The projector augmented wave (PAW) method was used to describe electronion interactions, 36 while the generalized gradient approximation using the Perdew-Burke-Ernzerhof (PBE) functional was used to describe the electron exchange correlation. The valence electrons were taken to be 2s 2 2p 4 for O and 6s 2 5d 4 for W. The valence electron wave functions were expanded using a double-z basis set. The convergences with respect to the basis set, the cutoff energy, and the k point mesh have been tested and the cutoff energy and the k-point mesh used in this work are appropriate for the system.…”
Section: Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The projector augmented wave (PAW) method was used to describe electronion interactions, 36 while the generalized gradient approximation using the Perdew-Burke-Ernzerhof (PBE) functional was used to describe the electron exchange correlation. The valence electrons were taken to be 2s 2 2p 4 for O and 6s 2 5d 4 for W. The valence electron wave functions were expanded using a double-z basis set. The convergences with respect to the basis set, the cutoff energy, and the k point mesh have been tested and the cutoff energy and the k-point mesh used in this work are appropriate for the system.…”
Section: Calculationmentioning
confidence: 99%
“…The ability to synthesize crystalline photocatalysts with well-defined crystallographic orientations allows fundamental comparative studies to be carried out, which in turn help in establishing defensible relationships between the surface atomic structures and photochemical properties. [4][5][6] Photocatalysts in the forms of nanoparticles and thin films have been synthesized for this purpose. These include nanoparticles of TiO 2 samples with preferentially exposed (001) or (101) crystal planes, 5,7 ZnO(001), 8 BiVO 4 nanosheets mainly consisting of {100} orientations, 9 Ag 3 PO 4 dodecahedra with only {110} facets exposed and cubes bounded entirely by {100} facets, 10 and WO 3 nanocrystals with {110} and {111} facets exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Among oxides, the surface of rutile TiO 2 (110) is one of the most thoroughly studied, both experimentally and theoretically, and has served as a prototypical model for fundamental studies of reducible metal oxides [3][4][5][6][7]. This study details the adsorption and desorption of a series of small (C 1 -C 4 ) hydrocarbons (n-alkanes, 1-alkenes, and 1-alkynes) on TiO 2 (110).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Acharya and co-workers reported that Ti 5c -bound EG (EG Ti ) molecules can dissociate into Ti 5c -bound hydroxyethoxy (HO–(CH 2 ) 2 –O Ti ) and OH b easily on R-TiO 2 (110) at ∼125 K, and a dynamic equilibrium between EG Ti molecules and dissociated HO–(CH 2 ) 2 –O Ti groups is observed with high-resolution scanning tunneling microscopy (STM) However, EG Ti adsorbs on R-TiO 2 (110) in the molecular form at ∼80 K, suggesting that the dissociation equilibrium of EG Ti is strongly dependent on the surface temperature.…”
Section: Resultsmentioning
confidence: 99%
“…), surface chemistry of simple alcohol molecules on R-TiO 2 (110) has been widely investigated not only for studying reaction mechanisms of important catalytic reactions but also for understanding chemical properties of TiO 2 . The surface chemistry of ethylene glycol (HOCH 2 CH 2 OH, EG), which is the simplest diol, on R-TiO 2 (110) is much more complicated than that of monohydric alcohols. Even without ultraviolet (UV) light irradiation, EG molecules can decompose into ethylene (C 2 H 4 ) and acetaldehyde (CH 3 CHO) on R-TiO 2 (110) at about 550–750 K, and the reaction channels are strongly EG coverage-dependent . Likewise, the photochemistry of EG on the reduced R-TiO 2 (110) surface is also coverage-dependent.…”
Section: Introductionmentioning
confidence: 99%